Expanding access to financial services: where do we go from here? - Mor, Nachiket (2005)
Despite a plethora of initiatives, it is estimated that over 500 million people in India continue to have no access to financial services. While ensuring the accessibility of such services does not constitute the sole panacea for economic growth, there are definite causal links between ensuring such increased access, growth and poverty reduction. To make real progress on this front, India needs to redraft its current approach to providing financial services. Steps that are tailored to meet local needs for finance need to be worked out by drawing on past experiences and studying those adopted by other countries. However, three steps are vital as preliminary requirements, (i) increased sophistication in bank regulation, (ii) development of basic financial services infrastructure, and (iii) an adaptive regulatory framework. - Reproduced.
Keywords: Financial institutions